Effect of GSDMB polymorphism on sensitivity to chemoradiation therapy for cervical cancer - Ni Zhong; Yi Yu; Guihua Pan; Huake Liu; Haizhi Zhou; Yongbin Zou; Hui Cao; Qinyu Tian; Huan Liu; Qin Peng (IMR Press, 2021)
Background: To investigate the effects of GSDMB polymorphism on sensitivity to chemoradiation. Methods: 108 cervical cancer patients were selected and treated with a combination of radiotherapy and chemotherapy. After 2 cycles, patients were grouped into sensitive group and non-sensitive group based on the chemoradiation therapy outcomes. GSDMB polymorphism was assessed by high-resolution melting (HRM) analysis, and the GSDMB gene expression was detected using RT-qPCR. Results: Our results indicate that the allele and genotype distribution of GSDMB in patients from sensitivity group were significantly different as compared to non-sensitive group. Experimental analysis showed a close correlation between GSDMB polymorphism and sensitivity to chemoradiation therapy for cervical cancer. Moreover, ATT, GCC, GCT and GTC halotype of GSDMB gene was significantly different among sensitive and non-sensitive groups (p < 0.05). Finally we found that GSDMB polymorphism was associated with GSDMB gene expression (p < 0.05). Conclusions: Our study concluded that GSDMB polymorphism has a distinct impact on sensitivity to chemoradiation therapy for cervical cancer. Collectively, this analysis provides new insights into the genetic causes of cervical cancer, and influences the overall prevention and treatment of cervical cancer.